2011
DOI: 10.1093/annhyg/mer105
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Pathogenic Bacteria and Antimicrobial Resistance in Bioaerosols from Cage-Housed and Floor-Housed Poultry Operations

Abstract: Most bacteria are more concentrated and most AMR genes are more prevalent in bioaerosols of FH poultry operations, where growth-promoting antibiotics may be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Most research currently focuses on the search for microorganisms in the aquatic environment. However, there is also growing interest in the presence of antibiotic resistance genes among bioaerosol microorganisms in work premises [ 77 , 78 , 79 ]. It is worth noting the potential of microorganisms in office bioaerosols, which, with their concomitant biofilm capacity, may inhabit air filters in air conditioners or other available moist surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Most research currently focuses on the search for microorganisms in the aquatic environment. However, there is also growing interest in the presence of antibiotic resistance genes among bioaerosol microorganisms in work premises [ 77 , 78 , 79 ]. It is worth noting the potential of microorganisms in office bioaerosols, which, with their concomitant biofilm capacity, may inhabit air filters in air conditioners or other available moist surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, they demonstrated that antibiotic preparations might act as delivery systems for their cognate ARG. Just et al [ 148 ] found bacitracin-resistance, erythromycin-resistance, and tetracycline resistance genes in bioaerosols from poultry operations, particularly in floor-housed farms. Also, genes associated with erythromycin and quinupristin-dalfopristin resistance, including erm B, erm A, msr C, and msr A/B, as well as mobile genetic elements related to the conjugative transposon Tn916 , have been found in bacterial isolates recovered from flies collected at poultry feeding operations [ 142 ].…”
Section: Antibiotic Resistance and Antibiotic-resistant Bacteria Imentioning
confidence: 99%
“…Our study showed that air sampling indoor air of poultry houses together with shotgun metagenomic sequencing can be used to detect pathogenic microorganisms. This approach can be used to study a various of pathogens, moulds, antimicrobial resistence in environments where a high hygiene standard is required [19, 47]. These findings indicate that in l.e.…”
Section: Discussionmentioning
confidence: 99%